The evaluation and importance of Newcastle disease’s economic loss in commercial layer poultry (Journal of Poultry Sciences and Avian Diseases, 2024)
Velogenic Newcastle disease virus (VNDV) causes a highly contagious and devastating disease in poultry and causes up to 100 percent mortality in susceptible populations during devastating outbreaks. Newcastle disease causes heavy economic losses to the global poultry industry by decreasing the growth rate, decreasing egg production, and increasing morbidity and mortality. The households face substantial economic losses throughout the year due to Newcastle disease. It is ranked first among other poultry diseases in village chickens. The economic losses caused by this disease in the poultry industry have given awareness about the importance of Newcastle disease and made it easier to justify the operations against this disease. So, estimating the economic losses caused by Newcastle disease is very important. Regarding the Newcastle disease's huge impact on production and causing a lack of eggs, we will have to compensate for this reduction by importing eggs from other countries. Hence, a tremendous amount of money will be needed to compensate for the shortage of eggs, which will result in a huge economic loss. Finally, these will directly affect the poultry industry and its financial resources, which clarifies the importance of correct and on-time vaccination and caring for Newcastle disease in poultry flocks to prevent enormous economic losses. In this study, the economic impact of Newcastle Disease on egg-laying farms was quantitatively assessed. Data were collected on the total number of egg-laying poultry monthly and annually. Subsequently, the economic loss for each period was calculated based on the total production period. The minimal damage caused by this disease is about 116,591 Tons. Summing all these periods' production decreases, the total loss will be 10538 Tons. To estimate the losses of the disease, it is necessary to estimate the losses in breeding herds and broiler herds so that the loss resulting from the endemic Newcastle disease of the country can be measured.